Systematic consumption risk in currency returns. (June 2017) - Hoffmann, Mathias; Studer-Suter, Rahel
Abstract: We sort currencies into portfolios by countries' past consumption growth. The excess return of the highest- over the lowest-consumption-growth portfolio – our consumption carry factor – compensates for negative returns during world-wide downturns and prices the cross-section of portfolio-sorted and of bilateral currency returns. Empirically, sorting currencies on consumption growth is very similar to sorting currencies on interest rates. We interpret these stylized facts in a habit formation model: sorting currencies on past consumption growth approximates sorting on risk aversion. Low (high) risk-aversion currencies have high (low) interest rates and depreciate (appreciate) in times of global turmoil.